Implementasi Moderisasi Beragama Dipondok Pesantren dalam Manajemen Pendidikan Islam - Ridha Yumna; Ilma Nur Cahayani; Siti Hafiza (Publikasi Indonesia, 2023)
The rise of radicalism, religious intolerance as well as violence in the name of religion in Indonesia over the last decade has concerned educational institutions, particularly Islamic educational institutions in Indonesia. The Indonesian state ideology, or Pancasila, emphasizes living in harmony among religious communities. It can even be said that Indonesia has become an example for other nations in successfully dealing with cultural and religious diversity and is considered successful in religious harmony as well as in the state. Conflicts or social problems sometimes still arise, but we can always solve them and also get back the benefits of unity and unity as a nation that should be great. Religious moderation is the essence of religion and its implementation is needed to create harmony within and between religions. So the spirit of religious moderation is actually about finding common ground between the two extreme poles, whether the extreme right or ultraconservative or extreme left or ultraliberal. Moderation in the Islamic style assumes that Muslims can respond to differences in religion or their respective sects. From the point of view of religious moderation, practicing religion is the same as fulfilling state obligations, just as fulfilling state obligations is a form of practicing religious teachings. These indicators are in the form of a national commitment, non-violence, tolerance and adaptation through local culture.